Shopping with violence: Black Friday sales in the British context. (November 2017) - Smith, Oliver; Raymen, Thomas
This article argues that the 2014 adoption of the US shopping tradition of Black Friday sales to stores and supermarkets in the United Kingdom and beyond represents an important point of enquiry for the social sciences. We claim that the importation of the consumer event, along with the disorder and episodes of violence that accompany it, are indicative of the triumph of liberal capitalist consumer ideology while reflecting an embedded and cultivated form of insecurity and anxiety concomitant with the barbaric individualism, social envy and symbolic competition of consumer culture. Through observation and qualitative interviews, this article presents some initial analyses of the motivations and meanings attached to the conduct of those we begin to understand as 'extreme shoppers' and seeks to understand these behaviours against the context of the social harms associated with consumer culture.